Design and development of copper based low-cost sensor for monitoring moisture in the fields. (2021) - Parashar, Vivek; Parashar, Amrita
Highlights: We have designed a low-cost sensor made from material easily available in the market. The designed sensor is cheap and cost-effective. Our sensor is more accurate than the sensors available in the market and also supports IoT. Abstract: In our research work, we have designed a soil resistivity sensor. This sensor will help us in calculating the electrical characteristics of soil, this, in turn, assists us in the formulation of soil's physical, chemical, and biological aspects. We created a low-cost sensor module out of a copper sheet. We have tested the soil of Gwalior and Bhopal district of Madhya Pradesh. We have deployed Wireless Sensor Network (WSN) and the data received from it is stored in the Thingspeak cloud for further processing using the Internet of Things.